Non-Destructive Imaging on Synthesised Nanoparticles - Elphick, Kelvin (Materials (Basel), 2021)
Our recently developed non-destructive imaging technique was applied for the characterisation of nanoparticles synthesised by X-ray radiolysis and the sol-gel method. The interfacial conditions between the nanoparticles and the substrates were observed by subtracting images taken by scanning electron microscopy at controlled electron acceleration voltages to allow backscattered electrons to be generated predominantly below and above the interfaces. The interfacial adhesion was found to be dependent on the solution pH used for the particle synthesis or particle suspension preparation, proving the change in the particle formation/deposition processes with pH as anticipated and agreed with the prediction based on the Derjaguin–Landau–Verwey–Overbeek (DLVO) theory. We found that our imaging technique was useful for the characterisation of interfaces hidden by nanoparticles to reveal the formation/deposition mechanism and can be extended to the other types of interfaces.